Effective response to intravitreal faricimab in a patient with myopic neovascular membrane resistant to aflibercept - Chamma Capelanes, Nelson; Moscovici, Bernardo K.; Regatieri, Caio V.; Sugai, Renata F. B.; Concer, Ana A. C. (Digital Journal of Ophthalmology, 2025)
A 56-year-old woman with pathological myopia and macular neovascularization in the right eye was treated with 20 intravitreal injections of aflibercept following a treat-and-extend protocol, with no significant clinical improvement. A single intravitreal injection of faricimab was administered, after which the patient showed complete resolution of subretinal fluid and reduced neovascular lesions. Her visual acuity improved from 20/200 to 20/80 in the right eye, and she remained stable for 9 months without further signs of neovascular activity. Faricimab, which targets both VEGF-A and Ang-2, may be an effective alternative in myopic neovascular membranes resistant to aflibercept. Larger studies are needed to explore the long-term efficacy of faricimab in treating pathological myopia.